45. Antimicrobial Stewardship for Urinary Tract Infection in Three Emergency Departments Across a Health System. (31st December 2020) - Shoff, Christopher; Funaro, Jason; Fischer, Kristen M; Boreyko, John; Shroba, Jenny; Mando-Vandrick, Jennifer; Liu, Beiyu; Lee, Hui-Jie; Spires, Steven S; Turner, Nicholas A; Theophanous, Rebecca; Staton, Catherine; et al.
Abstract: Background: Broad spectrum antibiotics are often prescribed to patients presenting to the emergency department (ED) for evaluation of urinary tract infection and pyelonephritis (UTI). We evaluated the effect of a target-specific antibiogram, education, and feedback on UTI diagnosis and antibiotic prescribing in this setting. Methods: We created a urine-specific antibiogram from patients seen and treated without admission at three ED locations (one academic and two community hospitals). We then provided a treatment algorithm and supplemental educational content to ED providers in November 2019. Educational content highlighted appropriate diagnosis, antibiotic selection, and treatment duration for UTI. Adult encounters with appropriate ICD-9/10 codes within twelve months prior to content delivery comprised the preintervention cohort. The postintervention cohort consisted of adult visits following educational intervention until April 17, 2020. During the postintervention phase (November 2019 to April 2020), summary data regarding UTI diagnoses and guideline-concordant prescriptions were fed back routinely to ED providers through email. Guideline-concordant prescriptions were defined as those adhering to first or second-line therapy in the treatment algorithm. The proportion of prescriptions meeting this definition fulfilled the primary outcome. An interrupted time series analysis measured changes in guideline concordance. Results: Data from 6, 713 distinct encounters were analyzed across the three sites. While guideline concordant prescribing increased following intervention at all locations (30.9% to 38.8%, 48.1% to 49.1%, and 48.2% to 59.6%), these increases were not statistically significant (Figures 1, 2, and 3). The proportion of all ED encounters with a UTI diagnosis did not differ following the intervention. Interestingly, guideline concordance was greater in the academic ED, compared to the community hospitals. Conclusion: Although guideline concordant prescribing for UTI increased in all three ED settings with education and email correspondence feedback, these results were not statistically significant. A variety of methods may be required to realize improved antibiotic prescribing across a diverse group of clinicians. Disclosures: Rebekah W. Moehring, MD, MPH, Agency for Healthcare Quality and Research (Grant/Research Support)Centers for Disease Control and Prevention (Grant/Research Support)